Prenatal health education using expository method as a prevention of stunting - Yunitasari, E; Maesaroh, S; Fauziningtyas, R; Emawati, A (International Journal of Psychosocial Rehabilitation, 2020)
As a global Issue since 2017, stunting is seen as a serious problem that should be solved immediately to reduce the prevalence of stunting. The incidence of stunting in Indonesia continues to increase, it is due to socio-ethnic conditions food belief especially in pregnant women in some regions. The aim of this study is to explain the influence of health education on pregnant women in preventing stunting. A quasy experiment with pre-post test design was conducted on 60 pregnant women in Bangkalan. A systematic simple random sampling technique was used to choose pregnant women with pregnancy